Pelatihan Manajemen Pengelolaan Emosi pada Ibu-Ibu PKK RT.02/RW.05 Gemah Pedurungan Semarang - Rusmalia Dewi; Gusti Yuli Asih; Yudi Kurniawan; Agung Santoso Pribadi (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
The purpose of this community service (PkM) is to provide training on Emotional Management for PKK mothers to increase their understanding of the importance of self-compassion related to emotions so that they can maintain their physical and mental health. This Emotional Management Training is a practical method in managing emotions, such as relaxation techniques, effective communication, and solving daily problems experienced by individuals when interacting with their environment, both family and social environments. PKK mothers RT.02/RW.05, Gemah sub-district, Pedurungan district, are mostly housewives. Emotional management is very necessary so that it does not last long, which in the end can affect the mother's mental health, so that the impact becomes even greater. To prevent these things from happening continuously, the PkM team of the psychology faculty provides assistance to the mothers by holding Emotional Management training which aims to maintain the mothers' mental health from pressures that arise both in the environment and from home. This input made the PkM team want to help find solutions regarding the development of self-skills for mothers through Emotional Management Training. The team's outreach to these mothers resulted in a 40% increase in their understanding of emotional management. By improving these mothers' skills, it is hoped that they will find it easier to control their emotions, focus, and better understand themselves and their surroundings, enabling them to overcome the challenges and obstacles they encounter in their daily lives.